Readmission After Lobectomy for Lung Cancer: Not All Complications Contribute Equally. Issue 1 (July 2021) - Brown, Lisa M.; Thibault, Dylan P.; Kosinski, Andrzej S.; Cooke, David T.; Onaitis, Mark W.; Gaissert, Henning A.; Romano, Patrick S.
Abstract : Objective: The aim of this study was to identify independent predictors of hospital readmission for patients undergoing lobectomy for lung cancer. Summary Background Data: Hospital readmission after lobectomy is associated with increased mortality. Greater than 80% of the variability associated with readmission after surgery is at the patient level. This underscores the importance of using a data source that includes detailed clinical information. Methods: Using the Society of Thoracic Surgeons (STS) General Thoracic Surgery Database (GTSD), we conducted a retrospective cohort study of patients undergoing elective lobectomy for lung cancer. Three separate multivariable logistic regression models were generated: the first included preoperative variables, the second added intraoperative variables, and the third added postoperative variables. The c statistic was calculated for each model. Results: There were 39, 734 patients from 277 centers. The 30-day readmission rate was 8.2% (n = 3237). In the final model, postoperative complications had the greatest effect on readmission. Pulmonary embolus odds ratio [OR] 12.34 [95% confidence interval (CI), 7.94–19.18] and empyema, [OR 11.66 (95% CI, 7.31–18.63)] were associated with the greatest odds of readmission, followed by pleural effusion [OR 7.52 (95% CI, 6.01–9.41)], pneumothorax [OR 5.08 (95% CI, 4.16–6.20)], central neurologic event [OR 3.67 (95% CI, 2.23–6.04)], pneumonia [OR 3.13 (95% CI, 2.43–4.05)], and myocardial infarction [OR 3.16 (95% CI, 1.71–5.82)]. The c statistic for the final model was 0.736. Conclusions: Complications are the main driver of readmission after lobectomy for lung cancer. The highest risk was related to postoperative events requiring a procedure or medical therapy necessitating inpatient care.